"Degradabilidad ruminal in-situ del pasto king grass (pennisetum purpureum) fertilizado con cuatro niveles de nitrogeno cosechado a los sesenta dias". - Arana Sánchez, Denisse Lizbeth (2018)
The field work of the present titration research project was carried out at the Pichilingue Tropical Experimental Station of the National Institute of Agricultural Research (INIAP) and at the Rumiology and Nutritional Metabolism laboratory of the State Technical University of Quevedo. The effect of nitrogen fertilization with urea (0, 25, 50 and 75 kg of N ha-1) on chemical composition (CQ) and in situ ruminal degradability (DIS) of dry matter (DISMS), organic was evaluated (DISMO) and bioavailability of the inorganic matter (BISMI-ash) of the King Grass grass harvested at 60 days of regrowth. For the statistical analysis of the CQ, a randomized complete blocks design was used and for the DIS one of the blocks was complete randomized generalized, where the blocking criteria were the fertility of the soil and the animal where the ruminal incubation was performed, respectively. It was observed that there was a higher MS content when the grass was fertilized with 75 kg of N ha-1 (P <0.05), however, it was not evident (P> 0.05) effect of the fertilization on the other variables of CQ. Although there were differences (P <0.05) between the studied treatments, no direct relation was observed of the effect of the nitrogen level applied to the soil on DISMS, DISMO and BISMI in the different incubation times, since several treatments had similar behaviors. The parameters of ruminal degradability (a, b, c, Kd and DE) for the MS, MO and MI, also did not report direct conclusive responses of the effect of nitrogen fertilization, since in some variables there was similarity with the control, while that in another it was found discrepancies, since it was concluded, that for the conditions in which the study was developed, there is no need for urea fertilization of King Grass grass. Key words: Degradability, Rumen, Rumiology, Fertilization, Nitrogen, Chemical composition.